2019
DOI: 10.20944/preprints201901.0331.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determining Symptomatic Factors of Nomophobia in Peruvian Students from the National University of Engineering

Abstract: The use of cell phones has increased worldwide in the past few decades, particularly in children and adolescents. Using these devices provides personal benefits. Communicating through cell phones was a very important factor in the socioeconomic progress of developed countries. However, it is beyond doubt that its indiscriminate use can accompany certain psychiatric disorders or cause some disorder in a person, within the phobic group of anxiety disorders called nomophobia—associated with anxiety, ner… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Factors such as people isolating themselves and limiting face-to-face communication, using the phone as a method of coping with stressful situations, and avoiding the negative emotions they experience in the virtual world are thought to contribute. Examining the studies on anxiety, symptomatic factors of nomophobia were identified as anxiety, compulsive smartphone use, and panic, in a study conducted on university students by Rosales-Huamani et al (2019). Therefore, individuals with nomophobia are expected to have a high level of anxiety.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Factors such as people isolating themselves and limiting face-to-face communication, using the phone as a method of coping with stressful situations, and avoiding the negative emotions they experience in the virtual world are thought to contribute. Examining the studies on anxiety, symptomatic factors of nomophobia were identified as anxiety, compulsive smartphone use, and panic, in a study conducted on university students by Rosales-Huamani et al (2019). Therefore, individuals with nomophobia are expected to have a high level of anxiety.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Studies carried out have proven that the level of nomophobia is high in young population 3,6,11 . Even though there are umpteen studies in the literature where women are generally more nomophobic, 12–14 so far there are no studies on whether the marital status and education have significant effects on nomophobia 15–18 …”
Section: Introductionmentioning
confidence: 99%
“…3,6,11 Even though there are umpteen studies in the literature where women are generally more nomophobic, [12][13][14] so far there are no studies on whether the marital status and education have significant effects on nomophobia. [15][16][17][18] 1.2 | The behaviors of smartphone use and nomophobia Today, smartphones have become an indispensable part of individuals' lives. In several research, it is stated that the time for daily smartphone use is between 4 and 5 h, and the more people get used to using smartphones, their periods of usage increases automatically.…”
mentioning
confidence: 99%
“…Nomophobia can affect various population groups, especially young people, whether they are university students (Bartwal and Nath, 2019;Farooqui et al, 2017) or at other educational stages (Rosales-Huamani et al, 2019). This occurs when people are unable to communicate and are disconnected from their virtual identity.…”
Section: Introductionmentioning
confidence: 99%